2019
DOI: 10.29252/rme.11.4.13
|View full text |Cite
|
Sign up to set email alerts
|

Clinical faculty membersُ attitude toward Medical Professionalism: A case study of Tehran University of Medical Sciences

Abstract: Introduction: The faculty members' attitude toward professionalism has a significant impact on conveying professional values to learners. The aim of this study was to assess the professional attitudes of the clinical faculty members of medical school in TUMS. Methods: In this cross-sectional study, 134 clinical faculty members of Tehran University of Medical Sciences using stratified sampling from different clinical departments were participated in 2017. The research tool was a 21-item questionnaire designed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 15 publications
4
6
1
Order By: Relevance
“…On the other hand, the t indices of the model were all within an acceptable range and con rmed the t and standardization of the model, it should be noted, that because surveying the experts, the proposed reforms were done in several stages, the t was good in this stage. The results of Agha Mohammadi et al (2017) showed that the professional attitude of medical professors in the indicators of enrichment, honor and honesty and respect are at the highest level and respectively in the indicators related to altruism and duty are at the lowest level (9). In the aforementioned study dimension of enrichment was in the rst rank and also in the current study, the dimension of enrichment is similarly in the rst rank.…”
Section: Discussion and Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…On the other hand, the t indices of the model were all within an acceptable range and con rmed the t and standardization of the model, it should be noted, that because surveying the experts, the proposed reforms were done in several stages, the t was good in this stage. The results of Agha Mohammadi et al (2017) showed that the professional attitude of medical professors in the indicators of enrichment, honor and honesty and respect are at the highest level and respectively in the indicators related to altruism and duty are at the lowest level (9). In the aforementioned study dimension of enrichment was in the rst rank and also in the current study, the dimension of enrichment is similarly in the rst rank.…”
Section: Discussion and Resultssupporting
confidence: 65%
“…A study by Campbell et al (2007) on 3504 practicing physicians in internal medicine, family practice, pediatrics, surgery, anesthesiology, and cardiology, found that the highest average was related to management of con icts of interest (8). In a study by Agha Mohammadi et al by assessing the attitudes of clinicians towards professionalism, he showed that the professional attitude of medical professors towards the indicators of enrichment, honor, integrity and respect are ranked the highest and the indicators related to altruism and accountability are ranked at the lowest level (9).…”
Section: Introductionmentioning
confidence: 99%
“…The clinical education is one of the most important courses in forming the professional identity of learners who learn in the experiential learning cycle through observation, repetition and reflection 10 . The present results showed the clinical teachers obtained the highest scores in the domain of doctor-patient relationship [19][20][21] . Similar to our results, the findings of studies indicated the clinical teachers had a positive attitude to integrity and honesty toward patients more than other stakeholders did.…”
Section: Discussionmentioning
confidence: 47%
“…Similarly, the study findings of Garshasbi indicated after the doctor-self relationship domain, the interprofessional relationship domain achieved the lowest scores 14 . In this regard, the results of Aghamohammadi's study showed the attitude of clinical teach-ers towards the cooperation among physicians and nurses were reported in the lowest level 19 . Despite the development of interprofessional training and collaboration in educational systems, challenges such as hierarchical relationships, doctor centeredness, and interdisciplinary discrimination were key barriers to implement team-based care in the investigated context 27 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation